MANAJEMEN ORGANISASI DALAM AL-QUR’AN (Kajian Qs. Ali Imran : 104 dalam Perpektif Manajemen Pendidikan Islam) - Irfan Afandi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2015)
Al-Quran is the holy book that provides guidance for mankind. With a viewing angle and a new perspective, al-Qur'an will be able to inspire humans. For humans, the Qur'an is a blessing and countless blessings. One scientific approach here is the study of the Koran in Islamic education management perspective. Islamic Education Management is a process of structuring or management of Islamic educational institutions that involve human resources Muslim and non-Muslim in a move to achieve the Islamic Educational effectively and efficiently. Organizations need the elements that support organizational sustainability. These elements lies in the structure of the system problems organization, organization cultural systems, individual system and the political system in the organization or organizations exist. Although an understanding of the Koran not to have a technical term (terminus tecnikus) in the academic community management assessment organizations exist, but the Quran also offers how the organization is able to walk. System - a system that contained in organization theory can be directed to get instructions through the verses of the Quran. Driven by a scientific theory is then people will not understand the Qur'an with coercion that are tailored to his wishes.